Review of Indonesia Revival: Focus on Timor - Lathrop, John P. (Pusat Studi Pentakosta Indonesia, 2021)
News of spiritual stirrings in the Christian church attract attention. Believers around the world are encouraged by such reports. These accounts hold out the hope that it can happen in other places and may prompt some to pray for just such a divine visitation. In the later part of the twentieth century Indonesia was the setting for one of these moves of God. A number of people have written about this revival, George W. Peters is one of them. In his book, Indonesia Revival Focus On Timor, he looks at the factors that he believes contributed to it as well as its strengths and weaknesses.Berita tentang gejolak rohani di gereja Kristen menarik perhatian. Orang-orang percaya di seluruh dunia didorong oleh laporan semacam itu. Kisah-kisah ini memberikan harapan bahwa hal itu dapat terjadi di tempat lain dan mungkin mendorong beberapa orang untuk berdoa untuk kunjungan ilahi seperti itu. Di bagian akhir abad kedua puluh, Indonesia adalah tempat untuk salah satu gerakan Tuhan ini. Sejumlah orang telah menulis tentang kebangkitan ini, George W. Peters adalah salah satunya. Dalam bukunya, Indonesia Revival Focus On Timor, ia melihat faktor-faktor yang menurutnya berkontribusi terhadapnya serta kekuatan dan kelemahannya.